Mekanisme Pembayaran Ganti Kerugian Dalam Ajudikasi Khusus Oleh Ombudsman Berdasarkan Peraturan Presiden Nomor 31 Tahun 2018 Tentang Mekanisme Dan Tata Cara Ajudikasi Khusus Dalam Upaya Penegakan Prinsip Good Governance - Mastur, Mastur; Salsabela, Yuliyana (Fakultas Hukum Universitas Wahid Hasyim, 2025)
This research is motivated by the suboptimal implementation of special adjudication by the Ombudsman of the Republic of Indonesia, particularly regarding the compensation payment mechanism for losses caused by maladministration in public services. Presidential Regulation Number 31 of 2018 serves as the legal foundation and addresses issues related to the mechanism in order to uphold the principles of good governance. The focus of this study is the compensation payment mechanism in special adjudication carried out by the Ombudsman of the Republic of Indonesia. The purpose of this research is to analyze the compensation payment mechanism and to identify obstacles in its implementation. The research employs a qualitative method aimed at analyzing phenomena experienced by the research subjects. A statutory approach is applied, specifically referring to Presidential Regulation Number 31 of 2018. The results of the study indicate that: (1) The compensation payment mechanism in special adjudication conducted by the Ombudsman of the Republic of Indonesia, based on Presidential Regulation Number 31 of 2018, begins with the issuance of a special adjudication decision by the Ombudsman—which is final and binding—and proceeds to the execution of compensation payment by the public service institutions proven to have committed maladministration. (2) The obstacles in implementing the compensation payment mechanism in special adjudication include limited budget, low awareness among government institutions, and lack of public knowledge. Moreover, the absence of strict sanctions against institutions that fail to implement adjudication decisions has hindered its effectiveness.